Pengaruh E-Kinerja dan Kompetensi terhadap Kinerja ASN di Korwil Dinas Pendidikan Kecamatan Sukomoro melalui Motivasi sebagai Variabel Intervening - Imroatul Chasanah; Eka Askafi; Nisa Mutiara (Universitas Islam Kadiri, 2022)
This research is motivated by the launch of a new innovation from BKN, namely E-Kinerja which is used as a monitoring of the performance of ASN employees, in accordance with Government Circular number 16/SE/VII/20205/SE/V/ 2020. Apart from the E-Kinerja system, other things that can be done are: influencing performance improvement is competence, both of which become important variables with the addition of an intervening variable, namely motivation which is still interesting to study. The purpose of this study is to analyze the effect of E-Kinerja and Competence on Performance. In addition, to analyze the effect of implementing E-Kinerja and Competence on Performance through Motivation. This study uses quantitative research methods with 31 employees as respondents. The data analysis method uses validity and reliability tests, while the classical assumption test uses heteroscedasticity test, multicollinearity test and normality test and is equipped with path analysis using trimming theory. The results of this study are E-Kinerja has no significant effect on motivation, competence has a significant effect on motivation, E-Kinerja has no significant effect on performance, competence has no effect on performance, motivation has a positive effect on performance. , E-Kinerja through motivation has an effect on performance, competence through motivation has an effect on performance.